Framework and strategy for integrated monitoring and evaluation of child health programmes for responsive programming, accountability, and impact. (30th July 2018) - Diaz, Theresa; Rasanathan, Kumanan; Meribole, Emmanuel; Maina, Isabella; Nsona, Humphreys; Aung, Kyaw Myint; Nemser, Bennett; O'Neill, Kathryn Patricia
Abstract : Stronger governance and leadership is needed to implement and maintain integrated reporting systems, say Theresa Diaz and colleagues